2023
DOI: 10.1021/acs.jafc.3c01220
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Adduct Formation between β-Lactoglobulin and Flavor Compounds under Thermal Treatments That Mimic Food Pasteurization or Sterilization

Abstract: Thermal processing (e.g., pasteurization and sterilization) is a critical step ensuring the microbial safety of our foods. Previous work from our laboratory has examined the covalent reactions occurring between proteins and a broad selection of flavor compounds under ambient storage temperatures (25−45 °C). However, similar research on reactions of flavor compounds with a protein under thermal processing conditions has not been investigated. In the current study, covalent adduct formation between βlactoglobuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…The reversible binding strength is dependent on the aroma compound's hydrophobicity, hence inducing variable effects on release and perception [7] that are exemplified in several of the results presented above (Table 1). Furthermore, if aldehydes are known to irreversibly bind to proteins through covalent binding, a recent study has shown that aroma compounds of various chemical classes may covalently bond to proteins during thermal processing through Schiff base, Michael addition, and disulfide linkages [145].…”
Section: The Food Matrixmentioning
confidence: 99%
“…The reversible binding strength is dependent on the aroma compound's hydrophobicity, hence inducing variable effects on release and perception [7] that are exemplified in several of the results presented above (Table 1). Furthermore, if aldehydes are known to irreversibly bind to proteins through covalent binding, a recent study has shown that aroma compounds of various chemical classes may covalently bond to proteins during thermal processing through Schiff base, Michael addition, and disulfide linkages [145].…”
Section: The Food Matrixmentioning
confidence: 99%